The effect of isorhamnetin glycosides extracted from Opuntia ficus-indica in a mouse model of diet induced obesity. Issue 3 (14th January 2015) - Rodríguez-Rodríguez, César; Torres, Nimbe; Gutiérrez-Uribe, Janet A.; Noriega, Lilia G.; Torre-Villalvazo, Iván; Leal-Díaz, Ana M.; Antunes-Ricardo, Marilena; Márquez-Mota, Claudia; Ordaz, Guillermo; Chavez-Santoscoy, Rocío A.; Serna-Saldivar, Sergio O.; Tovar, Armando R.
Abstract : An OFI extract rich in isorhamnetin glycosides prevents metabolic abnormalities associated with DIO. Abstract : A diet rich in polyphenols can ameliorate some metabolic alterations associated with obesity and type 2 diabetes. Opuntia ficus-indica (OFI) is a plant rich in isorhamnetin glycosides and is highly consumed in Mexico. The purpose of this research was to determine the metabolic effect of an OFI extract on a mouse model of diet-induced obesity and in isolated pancreatic islets. OFI extract was added to a high fat (HF) diet at a low (0.3%) or high (0.6%) dose and administered to C57BL/6 mice for 12 weeks. Mice fed the HF diet supplemented with the OFI extract gained less body weight and exhibited significantly lower circulating total cholesterol, LDL cholesterol and HDL cholesterol compared to those fed the HF diet alone. The HF-OFI diet fed mice presented lower glucose and insulin concentration than the HF diet fed mice. However, the HF-OFI diet fed mice tended to have higher insulin concentration than control mice. The OFI extract stimulated insulin secretion in vitro, associated with increased glucose transporter 2 (GLUT2) and peroxisome proliferator-activated receptor gamma (PPARγ) mRNA content. Furthermore, the OFI extract improved glucose tolerance, and additionally increased energy expenditure. These metabolic improvements were associated with reduced adipocyte size, increased hepatic IRS1 tyr-608 and S6 K thr-389 phosphorylation. OFI isorhamnetin glycosides also diminished the hepatic lipid content associated with reduced mRNA expression of the endoplasmic reticulum stress markers and lipogenic enzymes and increased mRNA expression of genes related to fatty acid oxidation. Overall, the OFI extract prevented the development of metabolic abnormalities associated with diet-induced obesity.